Internationalization of kaizen of gaming- in-depth analysis of Denmark and Lr on market selection of small firms - Sousa, Francisco José Brazete de (2022)
Kaizen Gaming is an online gambling company based in Greece, which operates under two brands, Stoiximan and Betano, holding a solid international experience. A strategic analysis of the company “status quo” was performed testing domestic and external factors impacting Kaizen´s business model. Following Kaizen´s expansion prospects under Betano, the brand to be internationalized, five potential countries were evaluated backed with macro data and qualitative industry-specific factors. Ultimately, both financial projections and marketing plan were performed to demonstrate the potential expansion conditions of Denmark, the chosen country. Hence, in light of the future prospects, the group outlined setting distinctive Partnerships and Marketing campaigns, to be aligned with technological trends adapting Betano into a blockchain based casino and seeking uncharted markets. The report is complemented with a literature review on International Market Selection for small firms and an in-depth analysis of Netherlands, one of the potential target countries.